The Management of Indonesian Navy Personnel Based on Competence to Achieve More Optimum Performance (International Journal of Scientific Research and Management (IJSRM), 2018)
The importance of the role of Human Resource management that is closely related to performance, in this case is the Indonesian Navy personnel. There is a must-have for every personnel to improve the optimal performance of competence development. The problem discussed in this research is how to improve the performance of Navy Personnel. The purpose of this research is to know the relation of competence to Navy performance support instrument and to analyze the influence of Human Resources on Navy performance. The method used is descriptive analysis of the influence of Human Resources on performance. Based on the results of the study, a person with adequate experience and technical qualifications, not necessarily have good performance, if the concerned is unable to show the behavior that supports the implementation of the task.